Novel multitarget analgesic candidate SZV-1287 demonstrates potential disease-modifying effects in the monoiodoacetate-induced osteoarthritis mouse model - Horváth, Ádám István; Bölcskei, Kata; Szentes, Nikolett; Borbély, Éva; Tékus, Valéria; Botz, Bálint; Rusznák, Kitti; Futácsi, Anett; Czéh, Boldizsár; Mátyus, Péter; Helyes, Zsuzsanna (Frontiers in Pharmacology, 2024)
Introduction: Monoiodoacetate (MIA)-induced osteoarthritis (OA) is the most commonly used rodent model to test anti-OA drug candidates. Here we investigated the effects of our patented multi-target drug candidate SZV-1287 [3-(4,5-diphenyl-1,3-oxazol-2-yl) propanal oxime] which is currently under clinical development for neuropathic pain, and characterized the model with complex functional, in vivo imaging and morphological techniques. Methods: Knee OA was induced by intraarticular MIA injection (0.5 and 0.8 mg). Spontaneous pain was assessed by weight distribution, referred pain by paw mechanonociception (esthesiometry), edema by caliper, neutrophil myeloperoxidase activity by luminescence, matrix metalloproteinase activity, vascular leakage and bone remodeling by fluorescence imaging, bone morphology by micro-CT, histopathological alterations by semiquantitative scoring, glia activation by immunohistochemistry. SZV-1287 (20 mg/kg/day) or its vehicle was injected intraperitoneally during the 21-day period. Results: MIA induced remarkable weight bearing and paw withdrawal threshold decrease, tibia and femur structural bone alterations (reactive sclerosis, increased trabeculation and cortical erosions), histopathological damage (disorganized cartilage structure, hypocellularity, decreased matrix staining and tidemark integrity, increased synovial hyperplasia and osteophyte formation), astrocyte and microglia density in the lumbar spinal cord. Major differences were not observed between the two MIA doses in most outcome measures. SZV-1287 inhibited MIA-induced weight bearing reduction, hyperalgesia, edema, myeloperoxidase activity, histopathological damage, astrocyte and microglia density. Conclusions: SZV-1287 may have disease-modifying potential by exerting analgesic, anti-inflammatory and chondroprotective effects. The MIA model is valuable for investigating OA-related mechanisms and testing compounds in mice with the optimal dose of 0.5 mg.